Academic Language Across Content Areas: Lessons From an Innovative Assessment and From Students' Reflections About Language. Issue 4 (6th May 2016) - Uccelli, Paola; Phillips Galloway, Emily
Abstract: Educators are aware of the need to promote students' academic language to support text comprehension. Yet, besides teaching academic vocabulary, many educators continue to ask, What would this instruction entail? Guided by a new framework known as core academic language skills (CALS), the authors' research focuses on delineating core language skills that contribute to reading comprehension to make them more visible to educators and researchers. In this article, findings from two studies are integrated to argue for a mixed‐methods approach to advance academic language research and pedagogy. In study 1, the authors assessed upper elementary/middle school students' CALS and quantitatively examined the association between CALS and reading comprehension. In study 2, the authors used qualitative methods to collect and analyze students' oral reflections about academic language. Key findings from these studies and their implications for academic language pedagogy in today's schools are discussed.